The Role of Workforce Quality, Village Assistance, and Village-Owned Enterprises on Economic Efficiency - Sawaroh; Idialis, Alifah Rokhmah; Yulistyono, Herry; Prabowo, Tripitono Adi (LifeSciFi, 2025)
Economic inefficiency in Pamekasan Regency is reflected in its low GRDP per capita, indicating suboptimal community welfare, particularly in villages. This study aims to analyze and identify village-level economic efficiency influenced workforce quality, village assistance, and the role of village-owned enterprises. Using a quantitative approach, this research applies an output-oriented Data Envelopment Analysis (DEA) method. The findings reveal that 71% of the villages have Constant Return to Scale (CRS), 7% are in Increasing Returns to Scale (IRS), and 22% in Decreasing Returns to Scale (DRS). The average efficiency score is 0.94, indicating that economic efficiency has reached 94%. This suggests that the combination of workforce quality, assistance, and village-owned enterprises involvement contributes significantly to achieving efficient village economies. The study concludes that while the economic efficiency level is high, a 6% improvement remains possible through increased output or reduced input, following the benchmark of optimally efficient Decision-Making Units (DMUs). The novelty of this research lies in its integration of qualitative elements quantified through efficiency measurement tools, providing a focused analysis of how workforce quality, village assistance, and village-owned enterprises institutions influence village-level economic efficiency.